2020
DOI: 10.2471/blt.19.250068
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine to deliver diabetes care in low- and middle-income countries: a systematic review and meta-analysis

Abstract: Objective To determine the effectiveness of telemedicine in the delivery of diabetes care in low- and middle-income countries. Methods We searched seven databases up to July 2020 for randomized controlled trials investigating the effectiveness of telemedicine in the delivery of diabetes care in low- and middle-income countries. We extracted data on the study characteristics, primary end-points and effect sizes of outcomes. Using random effects analyses, we ran a series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 52 publications
0
15
0
1
Order By: Relevance
“…For example, according to a systematic review and meta-analysis by Zhai and colleagues, 33 a statistically significant reduction in the HbA1c level in the telemedicine group compared with that of the control group was reported (pooled mean difference = −0.37, 95% CI = −0.49 to −0.25, p < 0.001). Moreover, a recent meta-analysis by Correia and colleagues, 36 which focused on telemedicine interventions implemented in low- and middle-income countries, indicated that telemedicine interventions were effective for diabetes management and resulted in significant reductions in HbA1c levels (standardized mean differences = −0.38, 95% CI = −0.52 to −0.23). In a study from Japan, Onishi and colleagues 39 reported that among patients with diabetes having HbA1c ⩾ 7% before the pandemic outbreak, providing diabetes care through telemedicine during the state of emergency resulted in an improvement to HbA1c < 7% after the emergency period in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, according to a systematic review and meta-analysis by Zhai and colleagues, 33 a statistically significant reduction in the HbA1c level in the telemedicine group compared with that of the control group was reported (pooled mean difference = −0.37, 95% CI = −0.49 to −0.25, p < 0.001). Moreover, a recent meta-analysis by Correia and colleagues, 36 which focused on telemedicine interventions implemented in low- and middle-income countries, indicated that telemedicine interventions were effective for diabetes management and resulted in significant reductions in HbA1c levels (standardized mean differences = −0.38, 95% CI = −0.52 to −0.23). In a study from Japan, Onishi and colleagues 39 reported that among patients with diabetes having HbA1c ⩾ 7% before the pandemic outbreak, providing diabetes care through telemedicine during the state of emergency resulted in an improvement to HbA1c < 7% after the emergency period in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Before the pandemic, many studies indicated the clinical effectiveness of telemedicine in diabetes care, including significant and clinically relevant reductions in HbA1c. [31][32][33][34][35][36][37][38] Moreover, during the COVID-19 pandemic, two studies from Japan 39 and Saudi Arabia 40 reported similar positive clinical outcomes in terms of glycemic control. In addition, it has been shown that increasing patient contact through frequent phone calls improves patient therapy adherence, motivation, and metabolic control.…”
Section: Introductionmentioning
confidence: 99%
“…Third, while awaiting immunization delivery and administration for individuals with diabetes, the care of patients with diabetes should continue to be adapted to optimize care continuity while mitigating the risk of SARS-CoV-2 exposure, such as through the use of telemedicine and mobile health platforms (37).…”
Section: Discussionmentioning
confidence: 99%
“…Second, strategies for the timely and equitable distribution and administration of COVID-19 vaccines, which have been primarily allocated to high-income countries [34] , should consider the high concurrent burden of diabetes and COVID-19 in LMICs and improve allocation efforts to reach those at highest risk living in lower resource contexts. Third, while awaiting immunization delivery and administration for individuals with diabetes, the care of patients with diabetes should continue to be adapted to optimize care continuity while mitigating the risk of SARS-CoV-2 exposure, such as through the use of telemedicine and mobile health platforms [35] .…”
Section: Discussionmentioning
confidence: 99%
“…In developed countries, change in governance and relaxation of regulations from professional and regulatory agencies in conducting video consultation have been observed during this public health emergency [ 4 ]. Evaluation of telemedicine has found it to be convenient to patients [ 5 , 6 ], improve their intermediate outcome [ 7 ], and be cost-effective [ 8 ] and cost-saving [ 9 ].…”
Section: Introductionmentioning
confidence: 99%